Mechanical Power during Veno-Venous Extracorporeal Membrane Oxygenation Initiation: A Pilot-Study - Belliato, Mirko (Membranes (Basel), 2021)
Mechanical power (MP) represents a useful parameter to describe and quantify the forces applied to the lungs during mechanical ventilation (MV). In this multi-center, prospective, observational study, we analyzed MP variations following MV adjustments after veno-venous extra-corporeal membrane oxygenation (VV ECMO) initiation. We also investigated whether the MV parameters (including MP) in the early phases of VV ECMO run may be related to the intensive care unit (ICU) mortality. Thirty-five patients with severe acute respiratory distress syndrome were prospectively enrolled and analyzed. After VV ECMO initiation, we observed a significant decrease in median MP (32.4 vs. 8.2 J/min, p < 0.001), plateau pressure (27 vs. 21 cmH(2)O, p = 0.012), driving pressure (11 vs. 8 cmH(2)O, p = 0.014), respiratory rate (RR, 22 vs. 14 breaths/min, p < 0.001), and tidal volume adjusted to patient ideal body weight (V(T)/IBW, 5.5 vs. 4.0 mL/kg, p = 0.001) values. During the early phase of ECMO run, RR (17 vs. 13 breaths/min, p = 0.003) was significantly higher, while positive end-expiratory pressure (10 vs. 14 cmH(2)O, p = 0.048) and V(T)/IBW (3.0 vs. 4.0 mL/kg, p = 0.028) were lower in ICU non-survivors, when compared to the survivors. The observed decrease in MP after ECMO initiation did not influence ICU outcome. Waiting for large studies assessing the role of these parameters in VV ECMO patients, RR and MP monitoring should not be underrated during ECMO.